Analisis Perlindungan Hukum Terhadap Konsumen Dalam Penyelenggaraan Cross-Border Payment Melalui Integrasi QR Code pada Kawasan ASEAN (RechtJiva, 2025)
This study examines the gaps in policy harmonization among ASEAN countries regarding cross-border transaction interoperability using QR codes and their dispute resolution mechanisms, in order to strengthen legal protection for consumers. The analysis is conducted normatively using statutory, historical, and conceptual approaches, referring to Article 2 (a), (b), and (c) of the ASEAN Agreement on Electronic Commerce, which emphasizes the importance of cross-border payment systems. The findings indicate that although there have been efforts at harmonization through bilateral cooperation and alignment with domestic laws, gaps remain in the implementation of local currency transactions that require structural alignment and integration into national regulations. In Indonesia, consumer protection is regulated under Bank Indonesia Regulations No. 3 of 2023 and No. 3 of 2024, but dispute resolution through alternative institutions still faces challenges such as high costs and complex procedures. Therefore, this study recommends the inclusion of standardized dispute resolution clauses and additional technical regulations from Bank Indonesia to enhance efficiency, fairness, and legal certainty for consumers in cross-border QRIS transactions.